Associations of neighborhood socioeconomic conditions with self-rated health, mental distress, and health behaviors: A nationwide cross-sectional study in Japan - Tomoya Hanibuchi; Tomoki Nakaya (Preventive Medicine Reports, 2020)
Although associations between neighborhood socioeconomic conditions and health have been well established, their geographical scope is mostly limited to Western societies, while multilevel studies in the non-Western context (e.g., Japan) are limited to specific cities/regions within countries. This consequently limits the external validity of the findings. To fill the gap, this study examined the associations between neighborhood socioeconomic conditions and health-related indicators by using nationwide cross-sectional data in Japan. Individual data was collected from a nationwide online survey conducted in 2015 (n = 4593). Self-rated health, mental distress (Kessler Psychological Distress Scale: K6), smoking, and physical activity were analyzed in relation to neighborhood conditions. Analyses of multilevel logistic regression models were done using the Areal Deprivation Index (ADI) with population density as the neighborhood-level independent variable. After adjusting for individual covariates, ADI showed significant positive associations with poor self-rated health (odds ratio for one standard deviation increase and 95% confidence interval: 1.09, 1.00–1.19), mental distress (1.09, 1.02–1.16), current smoking (1.11, 1.03–1.19), and physical inactivity (1.11, 1.04–1.18). Population density was not associated with the four dependent variables. Analyses of the nationwide survey data in Japan showed that neighborhood socioeconomic conditions were independently associated with multiple health statuses and behaviors. These analyses may contribute to generalizing existing findings. Lastly, the results indicate the importance of neighborhood socioeconomic conditions in reducing health disparities in Japan.